The Nuremberg Trials: International Criminal Law Since 1945 60th Anniversary International Conference - Reginbogin, Herbert R. (De Gruyter Saur, 2006)
60 years after the trials of the main German war criminals, the articles in this book attempt to assess the Nuremberg Trials from a historical and legal point of view, and to illustrate connections, contradictions and consequences. In view of constantly reoccurring reports of mass crimes from all over the world, we have only reached the halfway point in the quest for an effective system of international criminal justice. With the legacy of Nuremberg in mind, this volume is a contribution to the search for answers to questions of how the law can be applied effectively and those committing crimes against humanity be brought to justice for their actions.